Control of power converter used for electric vehicle DC charging station with the capability of balancing distribution currents and reactive power compensation - Moien A. Omar; Marwan M. Mahmoud (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The global interest in electric cars aims to achieve sustainability in the transportation sector and reduce dependence on conventional cars that mainly depend on fossil fuels, the main source of emissions polluting the environment. However, the electric cars required electric fast chargers to charge the batteries with high currents in order to make the electric cars competitive with conventional cars that required a short time for filling fuel. Single-phase electric chargers make the distribution feeders with unbalanced currents as the single-phase loads and single-phase PV inverters. In the case of the unbalanced operation, one of the three phases may reach its maximum limit before other phases which leads to disconnect the transformer and thereby inefficient and unreliable system operation. This paper presents a control scheme for a three-phase, four-leg power converter that can be used as a fast charger for electric cars. Moreover, it can be used for balancing grid currents and for reactive power compensation. This will avoid frequent interruptions of distribution transformers due to unbalanced operation and reactive power loads. The distribution feeder considered to evaluate the control scheme consists of single-phase loads and inverters in addition to the proposed converter. The converter controls the charging power effectively and balancing the feeder currents. Moreover, during off charging time which is a possible manner for the charging station when the EV battery is fully charged the converter is effectively used for unbalanced mitigation and reactive power compensation. The simulated results show the effectiveness of the proposed control scheme.